Stress hyperglycemia ratio and in-hospital prognosis in non-surgical patients with heart failure and type 2 diabetes - Zhou, Yiling; Liu, Li; Huang, Hongmei; Li, Nan; He, Jidong; Yao, Heling; Tang, Xiaochi; Chen, Xiangyang; Zhang, Shengzhao; Shi, Qingyang; Qu, Furong; Wang, Si; et al. (Cardiovascular diabetology, 2022)
Objective To evaluate the impact of stress hyperglycemia on the in-hospital prognosis in non-surgical patients with heart failure and type 2 diabetes. Research design and methods We identified non-surgical hospitalized patients with heart failure and type 2 diabetes from a large electronic medical record-based database of diabetes in China (WECODe) from 2011 to 2019. We estimated stress hyperglycemia using the stress hyperglycemia ratio (SHR) and its equation, say admission blood glucose/[(28.7 × HbA1c)− 46.7]. The primary outcomes included the composite cardiac events (combination of death during hospitalization, requiring cardiopulmonary resuscitation, cardiogenic shock, and the new episode of acute heart failure during hospitalization), major acute kidney injury (AKI stage 2 or 3), and major systemic infection. Results Of 2875 eligible Chinese adults, SHR showed U-shaped associations with composite cardiac events, major AKI, and major systemic infection. People with SHR in the third tertile (vs those with SHR in the second tertile) presented higher risks of composite cardiac events ([odds ratio, 95% confidence interval] 1.89, 1.26 to 2.87) and major AKI (1.86, 1.01 to 3.54). In patients with impaired kidney function at baseline, both SHR in the first and third tertiles anticipated higher risks of major AKI and major systemic infection. Conclusions Both high and low SHR indicates poor prognosis during hospitalization in non-surgical patients with heart failure and type 2 diabetes. Highlights Why did we undertake this study? Stress hyperglycemia is classic but a long-overlooked pathophysiological process and a recently validated parameter, stress hyperglycemia ratio (SHR), facilitates its estimation. What is the specific question(s) we wanted to answer? Is SHR associated with the in-hospital prognosis in non-surgical patients with type 2 diabetes and heart failure? What did we find? Compared to the nadir range of SHR at 0.79 to 1.08, both high and low SHR at admission elicit elevated risks of cardiac, kidney, and infectious adverse events during hospitalization in non-surgical patients with type 2 diabetes and heart failure. What are the implications of our findings? Clinicians should understand the inconsistency between the blood glucose at admission and HbA1c indicates poor prognosis during hospitalization and warrants additional monitoring.